DEVELOPMENT OF INTERNET OF THINGS (IoT) BASED FLEET MONITORING SYSTEM - LOY, KEN-JI (IRC, 2019)
A fleet management system is a system that has a communication and positioning module, or even an inclusion of additional car related module embedded in a vehicle in order to provide a backend monitoring and control system for the entire fleet operation. The main reasons fleet manageme nt system is imple me nted is, to solve the problem most logistic companies have which is to provide a better solution in controlling company’s vehicles and track down the activities of the company’s vehicles. In term of mainte na nce related aspect, it will include the vehicle fue l consumption rate based on real-time. A fleet management generally includes functionalities such as the monitoring of fleet locations, vehicle departure and arrival time estimation, generation of vehicle maintenance information and vehicle real-time information. For fleet management to work, there is a need for tools to be able to retrieve data and information from the vehicle. Thus, in this project, we are using a scanner tools to retrieve various vehicle related information from the car and then using those data, a microcontroller is used to send the data and compute the data before sending it to the server for further data analysation process. In addition to that, in this project, the accuracy of the data obtained from the scanner tools were also verified by executing field test. In addition, in order to verify the accuracy of the scanner tools in more detailed, the same field test, is conducted by having few variabilities of the test subject such as the driver, and car model. In the end of this field test, the differences in driving behaviour for all the drivers is explained detailly and is compared to each other based on the differences in RMSE and average fuel economy rate generated by each driver. Thus, by doing such project, it would greatly able to help fleet management companies to manage their own fleet vehicles more efficiently.